*The efficacy of the attachment-based SAFE® prevention program: a randomized control trial including mothers and fathers. Issue 5 (3rd September 2019) - Walter, I.; Landers, S.; Quehenberger, J.; Carlson, E.; Brisch, K. H.
ABSTRACT: SAFE® is a primary prevention program to promote secure infant-parent attachment. SAFE explicitly addresses mothers and fathers. In this current first study, efficacy was assessed in a low-risk German sample using a randomized control trial with an active control intervention. A high rate of fathers' participation was achieved: in SAFE 84.6% and in the control group intervention 73.9% of the fathers participated. Infant-parent attachment was assessed at the end of the year-long programs. There was a significant difference between groups in terms of secure infant-father attachment, but not of infant-mother attachment. In SAFE, 84.6% of the infants were securely attached to their father (n = 39), in comparison to 65.8% in the control group (n = 38). The proportion of secure infant-mother attachment was 66.7% in the SAFE group (n = 54) and 64.0% in the control group (n = 50). The program was successful in promoting infant-father attachment security.